2020
DOI: 10.1152/ajpendo.00023.2020
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute dual SGLT1/SGLT2 inhibition on incretin release and glucose metabolism after gastric bypass surgery

Abstract: Enhanced meal-related enteroendocrine secretion, particularly of glucagon-like peptide-1 (GLP-1), contributes to weight-loss and improved glycemia after Roux-en-Y gastric bypass (RYGB). Dietary glucose drives GLP-1 and glucose-dependent insulinotropic polypeptide (GIP) secretion postoperatively. Understanding how glucose triggers incretin secretion following RYGB could lead to new treatments of diabetes and obesity. In vitro, incretin release depends on glucose absorption via sodium-glucose cotransporter 1 (SG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The nutrient absorption from the gut appears to be more important for the gut hormone secretion compared to the exposure of the gut to nutrients [59,60]. Further evidence on the importance of glucose absorption on GLP-1 secretion after RYGB comes from a study where sodium glucose co-transporters-1 (SGLT-1), a major mechanism of dietary glucose absorption from the gastrointestinal tract, were blocked in people who have undergone RYGB through canagliflozin, a dual SGLT-1/SGLT-2 inhibitor [61]. The study found that indeed dual SGLT-1/SGLT-2 inhibition could reduce glucose absorption and subsequently reduce peak GLP-1 levels and insulin secretion after RYGB [61].…”
Section: Potential Explanations For the Increased Postprandial Gut Hormone Secretion From The Distal Gut After Rygb And Sgmentioning
confidence: 99%
“…The nutrient absorption from the gut appears to be more important for the gut hormone secretion compared to the exposure of the gut to nutrients [59,60]. Further evidence on the importance of glucose absorption on GLP-1 secretion after RYGB comes from a study where sodium glucose co-transporters-1 (SGLT-1), a major mechanism of dietary glucose absorption from the gastrointestinal tract, were blocked in people who have undergone RYGB through canagliflozin, a dual SGLT-1/SGLT-2 inhibitor [61]. The study found that indeed dual SGLT-1/SGLT-2 inhibition could reduce glucose absorption and subsequently reduce peak GLP-1 levels and insulin secretion after RYGB [61].…”
Section: Potential Explanations For the Increased Postprandial Gut Hormone Secretion From The Distal Gut After Rygb And Sgmentioning
confidence: 99%
“…These authors found that canagliflozin treatment reduced postprandial plasma glucose and insulin excursions during OGTT. More recently, Martinussen et al [13] suggested that SGLT-1-mediated glucose absorption contributed to incretin hormone secretion after RYGB. In this study, the authors showed a significant reduction in postprandial levels of glucose and insulin during OGTT using 600 mg of canagliflozin.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…It should be noted that in RYGB, the passage of nutrients from the gastric reservoir to the jejunum is accelerated up to 100 times, while the hypertrophy of the intestinal mucosa favors a faster absorption of glucose [5]. Recent trials have suggested the role of intestinal SGLT-1 in the pathophysiology of reactive hypoglycemia [13,14], and several studies have shown a dysregulation of these transporters in obesity, diabetes, or in patients having a high sugar diet [15,16]. Additionally, Nguyen et al [17] found an upregulation of intestinal glucose transporters, SGLT-1, after RYGB.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, alpha‐cell electrical activity decreases with increasing ambient glucose concentrations, meaning that SGLT1 activity presumably, as is the case for SGLT2 activity, plays a minor role in overall electrical regulation at higher glucose concentrations 58–60 . Interestingly, a recent human study showed that canagliflozin intake at a concentration that inhibits both SGLT1 and SGLT2 (600 mg) increased plasma glucagon concentrations 3‐4 hours after intake 63 . However, whether this effect resulted from a direct action on the alpha cell was unclear because it occurred much later than the maximum effects on urinary glucose excretion.…”
Section: A Role For Sglt1s In Normal Alpha‐cell Physiology?mentioning
confidence: 95%
“…[58][59][60] Interestingly, a recent human study showed that canagliflozin intake at a concentration that inhibits both SGLT1 and SGLT2 (600 mg) increased plasma glucagon concentrations 3-4 hours after intake. 63 However, whether this effect resulted from a direct action on the alpha cell was unclear because it occurred much later than the maximum effects on urinary glucose excretion. Furthermore, as already mentioned, a recent study on perifused human islets using the dual SGLT1/2 inhibitor, sotagliflozin, did not indicate effects of islet SGLT1 inhibition on glucagon output.…”
Section: A Role For Sglt1s In Normal Alpha-cell Physiology?mentioning
confidence: 99%